Visual patterns+multi-focus fisheye view: an automatic scalable visualization technique of data-flow visual program execution - Shizuki, B.; Toyoda, M.; Shibayama, E.; Takahashi, S. (Proceedings. 1998 IEEE Symposium on Visual Languages (Cat. No.98TB100254), 2002)
We present a scalable visualization technique for automatic animation of data-flow visual program execution. We also show a framework to assist programmers' browsing tasks by automatically producing the views of execution that highlight significant aspects of the program. The techniques described in this paper are based on the visual design patterns (VDPs) proposed in our VL'97 paper which serve as a flexible and high-level structure for reuse of visual parallel programming. This paper shows that VDPs also serve as a basis for representing aspects of the program, with which it is possible to provide scalable views and intelligent assistance for browsing dynamically created data-flow networks. We have incorporated these ideas into the visual tracer of the KLIEG visual parallel programming environment.